2014
DOI: 10.1051/bioconf/20140302015
|View full text |Cite
|
Sign up to set email alerts
|

Sequential fermentation using non-Saccharomycesyeasts for the reduction of alcohol content in wine

Abstract: Abstract. Over the last few decades there has been a progressive increase in wine ethanol content due to global climate change and modified wine styles that involved viticulture and oenology practices. Among the different approaches and strategies to reduce alcohol content in wine we propose a sequential fermentation using immobilized non-Saccharomyces wine yeasts. Preliminary results showed that sequential fermentations with Hanseniaspora osmophila, Hanseniaspora uvarum, Metschnikowia pulcherrima, Starmerella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…At this respect, sequential fermentations are being implemented in the food industry to obtain products with enhanced properties. This strategy allows the microorganism inoculated first to exert its metabolism without the influence of the subsequent microorganism . Ciani et al reported the duration of the interval between first and second inoculations as a key parameter to achieve the desired results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this respect, sequential fermentations are being implemented in the food industry to obtain products with enhanced properties. This strategy allows the microorganism inoculated first to exert its metabolism without the influence of the subsequent microorganism . Ciani et al reported the duration of the interval between first and second inoculations as a key parameter to achieve the desired results.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy allows the microorganism inoculated first to exert its metabolism without the influence of the subsequent microorganism . Ciani et al reported the duration of the interval between first and second inoculations as a key parameter to achieve the desired results. In our case, the length of this interval determines the value that the medium pH will have reached.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported lower ethanol yields using co-cultures of non-Saccharomyces -S. cerevisiae yeasts [19][20][21]. However, possible interactions between different yeast species in mixed fermentations could influence on final ethanol levels and oenological traits in wines.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these co-inocula under mixed conditions showed similar efficiency conversion than S. cerevisiae control ( Table 2). Several authors reported that a reduction in the alcohol level was achieved in fermentations using sequential inoculations [18][19][20][21]. In turn, these sequential inoculations showed better results when delay timing between non-Saccharomyces and S. cerevisiae yeasts was higher.…”
Section: Resultsmentioning
confidence: 99%
“…has led to the exploration of new species for winemaking. These non-conventional yeasts may contribute to the wine's flavor and taste by producing a broad range of secondary metabolites and extracellular enzymes (Hong and Park, 2013 ; Ciani et al, 2014 ; Wang et al, 2015 ). Some species could be interesting for alcohol level reduction in wine (Masneuf-Pomarede et al, 2010 ; Bely et al, 2013 ) or for greater fermentative ability in harsh conditions due to enhanced fructophily (Sutterlin, 2010 ; Magyar and Tóth, 2011 ).…”
Section: Introductionmentioning
confidence: 99%